Effect of cellulose nanofiber-based coating with chitosan and trans-cinnamaldehyde on the microbiological safety and quality of cantaloupe rind and fresh-cut pulp. Part 1: Microbial safety. (December 2020) - Zhang, Jin; Ozturk, Samet; Singh, Rakesh K.; Kong, Fanbin
Abstract: This study aimed to evaluate the effect of cellulose nanofiber (CNF)-based coating containing chitosan (CHI) and trans -cinnamaldehyde (TC) on microbial growth of foodborne pathogens and spoilage microorganisms on cantaloupe rind and fresh-cut pulp. Coated/uncoated cantaloupe rind and pulp samples were inoculated with Salmonella enterica, Escherichia coli O157:H7 and Listeria monocytogenes and subsequently subjected to storage for 20 d at 4 °C or 12 d at 22 °C. Results showed that coating with only CNF (0.5%, dry-base) was effective in the elimination of S. enterica and E. coli O157:H7. Adding CHI (1%, w/w) and TC (1%, w/w) into CNF-based coating enhanced film formation on the surface and increased the antimicrobial activity on rind sample, but the reduction effect was less significant on pulp samples. The CNF (0.5%, dry-base) +CHI (1%, w/w) +TC (1%, w/w) coating resulted in 2.23, 2.43 and 3.22 log10 CFU/cm 3 reduction of S. enterica, E. coli O157:H7 and L. monocytogenes, respectively, on pulp samples after 20 d at 4 °C. The formulation also significantly inhibited the growth of natural spoilage microorganisms, and no growth was observed up to 18 d at 4 °C. Results indicated that CNF-based coating significantly improved microbial safety of cantaloupe rind and fresh-cut pulp during storage by forming a physical barrier reducing activities of oxygen-dependent microorganisms. Highlights: CNF-based coating was developed for cantaloupe rind and fresh-cut pulp. CHI and TC improved the antibacterial effect of CNF-based coating. CNF-based coating as a physical barrier reduced oxygen availability. The growth of pathogens and spoilage microorganisms were significantly reduced.